2021
DOI: 10.3389/fpsyg.2021.647435
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Importance of Psychosocial Factors Associated With Sustainable Organizational Development During COVID-19

Abstract: Involvement in sustainable development is a voluntary activity. Organizations apply the principles of sustainable development only when they identify several benefits. These benefits are identified, especially with the financial ones. The involvement of organizations in sustainable organizations has different intensity levels. These intensity levels are influenced by psychosocial factors (PF), attitudes toward organizational risks, and organizational and urban policies. The present paper identifies the key psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Based on this conceptualization of sustainability, we further expanded the definition and value of sustainability in the HRD setting. Our analysis revealed that “sustainability” was the most frequently used term in 13 out of the 59 publications, without any other words added (Bianchi et al, 2022; Brandi & Thomassen, 2021; Dragan et al, 2021; Garbie, 2015; Kafetzopoulos, 2023; Kolk, 2016; Maltseva et al, 2019; Palthe, 2013; Sheehan et al, 2014; Valentin, 2015; Vodonick, 2018; Waite, 2013).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Based on this conceptualization of sustainability, we further expanded the definition and value of sustainability in the HRD setting. Our analysis revealed that “sustainability” was the most frequently used term in 13 out of the 59 publications, without any other words added (Bianchi et al, 2022; Brandi & Thomassen, 2021; Dragan et al, 2021; Garbie, 2015; Kafetzopoulos, 2023; Kolk, 2016; Maltseva et al, 2019; Palthe, 2013; Sheehan et al, 2014; Valentin, 2015; Vodonick, 2018; Waite, 2013).…”
Section: Resultsmentioning
confidence: 93%
“…Nations: Poland and Denmark (Zgrzywa-Ziemak & Walecka-Jankowska, 2021), United States (Craig & Allen, 2013; Eccles et al, 2014), Turkey (Cop et al, 2020; Özgül & Zehir, 2023), Greek (Kafetzopoulos, 2023), Canada (Vito et al, 2023), German (Wicki & Hansen, 2019), United Kingdom (Ipiranga & Aguiar, 2014), China (Abbas et al, 2022), Taiwan (Chan et al, 2022), Srilanka (Wijethilake & Upadhaya, 2020), Rome (Dragan et al, 2021), Brazil (Figueiredo et al, 2021), and Malaysia (Bilan et al, 2020; Yusoff et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations